Upaya Peningkatan Pengetahuan Remaja Terhadap Penyakit Paru Obstruktif Kronik (PPOK) dan Pengobatannya - Shalahuddin Al Madury; Endah Kurniawati; Sujono Riyadi; Ahmad Suyudi Rustam (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a growing health concern in Indonesia, compounded by rising smoking rates among adolescents. Increasing awareness among high school students about lung health, COPD risks, and available treatments is essential to promote healthier future generations. In response, a community service program entitled Goes to School was implemented to provide promotive and preventive health education aimed at enhancing adolescent knowledge and reducing the risk of COPD. The methods applied included interactive health education sessions, filling out pre-post-test questionnaires. The methods applied included interactive health education sessions, filling out pre-post-test questionnaires. The respondents of this program were all female (100%), with the majority aged 16 years (71.43%), and none reported being smokers. Evaluation results demonstrated an improvement in students’ knowledge levels, with mean scores increasing from 70.95 (pre-intervention) to 83.33 (post-intervention). Moreover, the proportion of students categorized as having very good knowledge rose from 38.10% to 80.95%, with the majority (62%) showing an upward shift in knowledge levels. These findings suggest that community service activities utilizing lecture and role-play methods positively impact students’ knowledge about COPD.